2017
DOI: 10.1145/3170472.3133842
|View full text |Cite
|
Sign up to set email alerts
|

A concurrency-agnostic protocol for multi-paradigm concurrent debugging tools

Abstract: Today's complex software systems combine high-level concurrency models. Each model is used to solve a specific set of problems. Unfortunately, debuggers support only the lowlevel notions of threads and shared memory, forcing developers to reason about these notions instead of the high-level concurrency models they chose.This paper proposes a concurrency-agnostic debugger protocol that decouples the debugger from the concurrency models employed by the target application. As a result, the underlying language run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In our experience, capturing this information requires typically a single line of code per token type. Marr et al [2017] demonstrated the use of AST tagging to a similar effect. Unfortunately, this requires many different AST tags, and will only highlight the body of functions and methods.…”
Section: Informational Featuresmentioning
confidence: 85%
“…In our experience, capturing this information requires typically a single line of code per token type. Marr et al [2017] demonstrated the use of AST tagging to a similar effect. Unfortunately, this requires many different AST tags, and will only highlight the body of functions and methods.…”
Section: Informational Featuresmentioning
confidence: 85%
“…Marr et al presented the Kómpos protocol [7], which is a concurrency-agnostic debugger protocol. Its goal is to decouple the debugger from the concurrency models such as threads, locks, communication event loops, and others.…”
Section: Recent Work On Idesmentioning
confidence: 99%
“…Kómpos [40] is an online debugger for SOMns. For debugging actor-based programs, Kómpos provides a wide set of message-oriented breakpoints and stepping operations.…”
Section: Debuggersmentioning
confidence: 99%